Efektifitas Sosialisasi Deteksi Dini Gangguan Bicara dan Bahasa untuk Guru di Lingkungan Sekolah Inklusi Kota Surakarta - Wiliyanto, Dian Atnantomi; Setyaningsih, Wiwik; Siswanto, Arif (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Speech and language disorders, if undetected, can affect a child's ability to express themselves, understand instructions, and actively participate in the learning process. This can lead to frustration, decreased self-confidence, and even social isolation. With the increasing number of inclusive schools accepting students with special needs, it is important for educators and health workers to have a deep understanding of early detection methods and effective intervention strategies. Objectives: to determine the effectiveness of early detection socialization in inclusive schools in Surakarta City on the competence of teachers in early detection of speech and language disorders. Methods: Community Service Program activities were carried out with a quantitative approach. The activity design uses a quasi-experimental approach. The sample was taken by proportional random sampling by looking at the length of service of teachers who have more than 3 years teaching Children with Special Needs in Inclusive Schools, so the sample used was 50 people, with the data collection technique using a test instrument and quantitative data analysis with SPSS. Results: The results of data analysis with SPSS show that the significance value is 0.000 (p value> 0.05), so it can be concluded that there is an effectiveness of socialization of the competence of early detection of speech and language disorders of teachers in Inclusive Elementary Schools in Surakarta City. The socialisation program carried out, as seen from the data analysis, shows a significant increase in teacher competence regarding early detection of speech and language disorders in students at school, with an average post-test score of 82.20 (high category). Conclusion: The results obtained indicate that there is an effectiveness of socialisation of the competence of early detection of speech and language disorders of teachers in Inclusive Elementary Schools in Surakarta City, with a high category. Keywords: early detection, inclusive schools, speech and language disorders, socialization, teachers